THE USE OF ENGLISH SONGS AND MOVIES IN EFL CLASSROOM - Hidayat, M. Aufa Bima (Teaching English as Foreign Language, Literature and Linguisticss, 2021)
It is often heard that English-language songs and films can improve students' English language skills. Many people suspect that when they see people who have good English skills, that person must have a hobby of listening to songs and watching films in English. This assumption is not entirely true, because someone who has good English skills might have other factors why he could speak English well. On the other hand, the statement is also not entirely wrong, many people who can speak English well claim to often hear songs and watch movies in English. But more than that, regardless of how or how to obtain English, the most important factor is the motivation and passion of everyone who wants to acquire English.